Library Digitalization Through the Provision of Facilities of Sekolah Indonesia Kuala Lumpur (SIKL)’S Library - Hasyim, Sirojuzilam; Irsad; Syafii, Muhammad; Sukardi; Rahman, Arif (Talenta Publisher, 2023)
The international community service activities carried out at the Sekolah Indonesia KualaLumpur aim to provide real benefits in the effort to create a digital library at SIKL which can increase interest in learning in children attending the Kuala Lumpur Indonesian School, Malaysia and as a learning medium that is more accessible and fun that in the future can create quality human resources and be able to compete in the era to come. KualaLumpur Indonesian School, Malaysia in the end with the international dedication carried out by the Postgraduate Lecturer in Economics through the program